Construction of CLEAs-lipase on magnetic graphene oxide nanocomposite: An efficient nanobiocatalyst for biodiesel production. (April 2019) - Badoei-dalfard, Arastoo; Karami, Zahra; Malekabadi, Saied
Graphical abstract: Highlights: maGO-CLEA-Lip reserve its total activity up to 5 cycles. maGO-CLEA-Lip reserve 75% of storage activity compare to free enzyme. maGO-CLEA-Lip showed 2.25 folds more affinity than free enzyme towards substrate. maGO-CLEA-Lip produced biodiesel 3.0 folds more than free enzyme. Abstract: In the present work, cross linked enzyme aggregates of Lipase (CLEAs-lip) was synthesized and immobilized on the magnetic amino functionalized graphene oxide (maGO-CLEAs-lip) nanocomposites. The immobilized lipase showed a broad range of temperature activity about 40–60 °C, as compared to free enzyme. In the case of maGO-CLEAs-lip nanocomposite, the observed lower K m value state 2.25 folds affinity for the p-nitrophenyl palmitate. Enzyme activity of maGO-CLEAs-lip nanocomposite was the highest up to 5 cycles. Storage stability results displayed maGO-CLEAs-lip retained about 75% of its original activity after 30 days of incubation. Remarkably, maGO-CLEAs-lip formed the highest biodiesel construction (78%) from R. communis  oil after 24 h of incubation. The biodiesel yield of this nanocomposite was 3.0 folds higher than free enzyme, making it talented as an excellent nanobiocatalyst for efficient production of biodiesel.